ANALISIS DAMPAK PENYELENGGARAAN KOTA SEHAT TERHADAP IPM KOTA BANJARMASIN TAHUN 2010-2017 - FARAH DIBA; SAIPUDIN SAIPUDIN (PPJP Universitas Lambung Mangkurat, 2019)
This study aims to determine the impact of the implementation of Healthy Cities on Banjarmasin City HDI in 2010 to 2017. So that the city government can find out how the impact of implementing healthy cities on HDI in Banjarmasin City as a first step in taking policies related to the implementation of healthy cities.The scope of this study was to analyze the impact of the implementation of a healthy city on the Banjarmason HDI in 2010-2017. The use of data analysis techniques in this study is descriptive, namely collecting, dividing, and deciphering the data obtained, then the objective results obtained from the problem of an analysis of the results of monitoring data.The results of this study indicate that the implementation of a healthy city has a positive impact on increasing the Human Development Index in Banjarmasin City. This can be seen from the increase in the Human Development Index of Banjarmasin City from year to year. Organizing healthy cities is also able to make health services better from year to year and can be felt well by the community.Keywords: Organizing Healthy Cities, Human Development Index, Banjarmasin City